PENGARUH IKLIM ORGANISASI, KOMITMEN ORGANISASIONAL DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. BPR KARANGWARU PRATAMA YOGYAKARTA - Kurniyati, Nany Noor (Optimum: Jurnal Ekonomi dan Pembangunan, 2013)
The objective of this research to know whether organizational climate organizational commitment and working satisfaction have the influence to employees performance. The research held in PT. BPR Karangwaru Pratama Mlati Sleman Yogyakarta. This research is quantitative by using method survey. Data collecting conducted through questionnaire and documentation. 45 employees determined as sampel in research or conceived of a census research. Technique analyse the data use the linear regression analysis and multiple linear regression. Result of research mention the organizational climate, komitmen organisasional and working satisfaction the employee own the positive and significant influence to employees performance at PT. BPR Karangwaru Pratama Yogyakarta. Level of influence of each variable that is organizational climate equal to 34,1%, organizational commitment give the influence equal to 57% and working satisfaction give the influence equal to 18,8%. Simultanly organizational climate, organizational commitment and working satisfaction own strong and significant influence to employee performance at PT. BPR Karangwaru Pratama Yogyakarta. This Matter is shown with the number of R square equal to 0,571 and number of significant Fcounted equal to 18,189 larger ones from number Ftable equal to 2,88 at level 0,05.